Understanding the Customer Multichannel Behaviour; The Role of Trust and Offline Image in Customer Movement Across Channels - Muhammad Rizwan; Muhammad Salman Azhar; Waseem Ahmad Khan; Shakeel Sarwar (Journal of Management Practices, Humanities and Social Sciences, 2021)
Due to the expectation of online sales growth around the world, the global online firms are continuously working to increase their existing customer base by attracting new customers to their online channel in driving sales growth. However, the adoption rate of ecommerce in the fashion industry is slow relative to other sectors and the primary reason for this slower adoption is due to the inability of translating the offline channel experience to the online channel. A structured questionnaire was used for the current study. The current study aims to understand the connection between offline trust and online trust. According to trust transfer theory, the trust can be transferred from one object to another object based on connection between these two objects. As both offline and online channel belongs to single company, the trust can be transferred from one channel to another channel. The results of the study confirmed the significant association between offline trust and online trust. Additionally, the offline image of the firm confirms the moderation between offline trust and online trust. Limitation of the study is only one channel related variable but in future researcher use many variables such as, channel enjoyment, channel related perceived risk, channel perceived value, and channel loyalty.